Visualizing coregency : an exploration of the link between royal image and co-rule during the reign of Senwosret III and Amenemhet III - Saladino Haney, Lisa, (Harvard Egyptological Studies;, 2020)
"In Visualizing Coregency, Lisa Saladino Haney explores the practice of co-rule during Egypt's 12th Dynasty and the role of royal statuary in expressing the dynamics of shared power. Though many have discussed coregencies, few have examined how such a concept was expressed visually. Haney presents both a comprehensive accounting of the evidence for coregency during the 12th Dynasty and a detailed analysis of the full corpus of royal statuary attributed to Senwosret III and Amenemhet III. This study demonstrates that by the reign of Senwosret III the central government had developed a wide-ranging visual, textual, and religious program that included a number of distinctive portrait types designed to convey the central political and cultural messages of the dynasty".